Rational Synthesis of Freestanding NaxV2O5-rGO Paper as the Stable Cathode for Sodium Ion Batteries - Wang, Qi; Li, Xin; Xu, Junmin; Yuan, Yueyue; Li, Xinyue; Wang, Xinchang (Frontiers in Materials, 2022)
The flexible NaxV2O5/rGO paper were successfully prepared via hydrothermal method followed by a vacuum filtration as a high-performance cathode for SIBs. The as-prepared NaxV2O5/rGO combine flexibility and high conductivity that can buffer the stress and facilitate the fast transportation of electrons during the charge-discharge process. As a result, the as-prepared NaxV2O5-rGO paper can exhibit a reversible Na-ion storage capacity of ∼197 mA h g−1 at 100 mA g−1 and a good cycling performance with 81% capacity retention for 400 cycles at high current density of 500 mA g−1, showing great potentials in flexible energy storage devices.